The Renewal of Teaching Ethics within the Digital Literacy Ecosystem: A Phenomenological Inquiry into the Professional Practices of Indonesian Teachers - fizi (TARBIYAH DARUSSALAM: JURNAL ILMIAH KEPENDIDIKAN DAN KEAGAMAAN, 2026)
This study examines how teachers reinterpret teaching ethics in the context of digital literacy-based education, by addressing gaps in previous studies that primarily viewed digital literacy as a technical skill. Using a qualitative phenomenological design, the study involved 80 teachers who were purposively selected and participated in digital learning practices. Data was collected through in-depth interviews, observations, and documentation, then analyzed using thematic coding, with stages of data reduction, data presentation, and conclusion drawn. The results of the study show that digital literacy is understood not only as a technological skill but also as an ethical foundation inherent in teachers' professional assessments. Five main themes emerged: ethical awareness formed by digital literacy, critical reflection on the use of technology, the construction of contextual ethical norms, the role of teachers as role models of digital ethics, and the need for institutional strengthening. Challenges include limited access to digital resources and lack of digital ethics training. This study offers a new theoretical contribution by integrating digital literacy as a contextual variable within the framework of teachers' professional ethics, while providing practical implications for policy development and teacher training in responding to ethical demands in the digital education era.